Aesthetic Expressions and Visual Experiences in Dunhuang Mural Paintings in Cultural and Creative Brands - Peng, Bo (Transactions on Social Science, Education and Humanities Research, 2023)
Through a comprehensive embroidery of the aesthetics of the art of painting, learn how the artists are curved and interesting to describe the life of the time, from the perspective of the composition, see how the traditional artists interpret the deep cultural significance and aesthesia of the Buddhist art story painting. By observing the rich visual experience and emotional resonance created by the composing elements, the composer provides a realistic creative method for the artistic design. At the same time, a new perspective for understanding the core elements of Eastern American art and the close relationship between the art composition and the emotion of the viewer. In the clash of traditional culture and modern literary design in China, dig out the real meaning of communicating excellent traditional culture.